2014
DOI: 10.2174/187231280801140929155351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Hepatocytes Under Prolonged Culture in a Novel Medium for the Maintenance of Hepatic Differentiation: Results with the Model Pro-inflammatory Cytokine Interleukin 6

Abstract: A major challenge for the evaluation of cytokine-induced down regulation of CYP gene expression in primary cultured hepatocytes is the spontaneous decrease in expression of the genes with culture duration. Based on our recent discovery that hepatocytes cultured for 7 days in a novel medium, Li's Differentiation Maintenance Medium (LDMM), would retain gene expression for markers of differentiation and most CYP isoforms at levels similar to those of the first day of culture, we examined the effects of the protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Following treatment with 1 ng/ml IL-6 for 24 h, CYP3A4 levels were decreased by 47% of the normal levels [40]. Compared to CYP2B6 and CYP3A4, the suppression of CYP2C9 expression is more resilient as it required 5 ng/ml IL-6 to lower the expression [40] by 65% [40]. The average EC 50 values for IL-6-driven downregulation of CYP3A4, CYP2B6, and CYP2C9 are 1.2, 1.9, and 3.6 ng/ml, respectively [40].…”
Section: Impact Of Cytokine and Other Inflammatory Proteins On Cyp Rementioning
confidence: 95%
See 3 more Smart Citations
“…Following treatment with 1 ng/ml IL-6 for 24 h, CYP3A4 levels were decreased by 47% of the normal levels [40]. Compared to CYP2B6 and CYP3A4, the suppression of CYP2C9 expression is more resilient as it required 5 ng/ml IL-6 to lower the expression [40] by 65% [40]. The average EC 50 values for IL-6-driven downregulation of CYP3A4, CYP2B6, and CYP2C9 are 1.2, 1.9, and 3.6 ng/ml, respectively [40].…”
Section: Impact Of Cytokine and Other Inflammatory Proteins On Cyp Rementioning
confidence: 95%
“…A study on human hepatocytes demonstrated that IL-6-mediated downregulation of CYP enzymes is a concentration-dependent phenomenon. Following treatment with 1 ng/ml IL-6 for 24 h, CYP3A4 levels were decreased by 47% of the normal levels [40]. Compared to CYP2B6 and CYP3A4, the suppression of CYP2C9 expression is more resilient as it required 5 ng/ml IL-6 to lower the expression [40] by 65% [40].…”
Section: Impact Of Cytokine and Other Inflammatory Proteins On Cyp Rementioning
confidence: 98%
See 2 more Smart Citations
“…Recently, a significant correlation between CRP and VCZ trough concentrations was reported . As in vitro studies have demonstrated that IL‐6 and other upstream proinflammatory cytokines downregulate CYP2C19 and CYP3A4 gene expression , downregulation of these CYP enzymes by elevated concentrations of IL‐6 might cause an increase in VCZ trough concentrations.…”
Section: Introductionmentioning
confidence: 99%